The effect of engine spin direction on the dynamics of powered two wheelers. Issue 4 (3rd April 2018) - Massaro, Matteo; Marconi, Edoardo
ABSTRACT: The effect of engine spin direction on the dynamics of powered two wheelers is investigated in terms of steady-state points (equilibria), vibration modes (stability), manoeuvre time (performance/manoeuvrability) and handling. The goal is to assess and quantify the advantage sometimes claimed for the 'counter-rotating' engine configuration, where the engine spins in the opposite direction with respect to wheels, against the 'conventional' configuration, where the engine spins in the same direction of wheels.